1991
DOI: 10.1002/pen.760310108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties in multidimensional composites

Abstract: The mechanical properties of three dimensional stitched composites were compared against those of the traditional two dimensional laminates. An attempt was made to correlate the change in properties to the change in the third directional fiber density. Tests conducted were the impact, three-point bending, damage tolerance, end notched flexure, and bending fatigue test. The results of these tests show that the third directional fibers can effectively inhibit delamination by increasing the interlaminar shear str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…After occurrence it develops due to working stresses of the laminate, leading to reduction in load capacity or even to destruction of the material. Such behaviour has been studied among others by Prichard and Hogg, 2 Liu, 3 Su, 4 Chung et al, 5 Jang et al, 6 Cantwell and Morton 7 and Hosur et al 8 The problem of delamination cracking reduces an application potential of the laminates. A number of solutions have been proposed to limit the formation and development of delamination cracks in the laminates.…”
Section: Theoretical Backgroundmentioning
confidence: 93%
“…After occurrence it develops due to working stresses of the laminate, leading to reduction in load capacity or even to destruction of the material. Such behaviour has been studied among others by Prichard and Hogg, 2 Liu, 3 Su, 4 Chung et al, 5 Jang et al, 6 Cantwell and Morton 7 and Hosur et al 8 The problem of delamination cracking reduces an application potential of the laminates. A number of solutions have been proposed to limit the formation and development of delamination cracks in the laminates.…”
Section: Theoretical Backgroundmentioning
confidence: 93%
“…Shear rigidity of LL orthogonal structure was found more than the angle interlock structures. 16 Several researchers have experimented and modelled the delamination behaviour of the laminated composites and observed that these composites delaminate easily under high impact 7,[17][18][19][20][21] and vibrations. Different weave designs, i.e., orthogonal through the thickness, LL angle interlock, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Core–shell polymers, such as acrylonitrile–butadiene–styrene copolymer (ABS), methyl methacrylate–butadiene–styrene copolymer, and acrylic impact modifiers, are one kind of important impact modifier for PA6 4–6. To modify the notch sensitivity and improve the notch impact strength of PA6, core–shell modifiers such as ABS have been used to successfully toughen PA6, and blends of PA6 and ABS materials are of significant commercial interest 7–23…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] To modify the notch sensitivity and improve the notch impact strength of PA6, core-shell modifiers such as ABS have been used to successfully toughen PA6, and blends of PA6 and ABS materials are of significant commercial interest. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In a previous study, 24 reactive monomers, such as acrylic acid, maleic anhydride (MA), and glycidyl methacrylate (GMA) grafted ABS copolymers, were synthesized and used to successfully toughen PA6 in our laboratory, and maleic anhydride functionalized acrylonitrile-butadiene-styrene copolymers (ABS-g-MAs) showed a much superior toughening ability. However, the achievement of supertough properties by an increase in the disperse-phase content sacrificed the stiffness of PA6, so the question of how to obtain PA6 blends with supertough and stiffer mechanical properties has become very meaningful.…”
Section: Introductionmentioning
confidence: 99%